Perspektif Hukum Lingkungan dalam Perlindungan Biodiversitas di Taman Nasional Gunung Ciremai - Damayanti, Ita; I, Ikomatussuniah (Media Hukum Indonesia (MHI), 2024)
Mount Ciremai National Park (TNGC) is an important conservation area that is home to a variety of endemic flora and fauna. This study examines the effectiveness of environmental law implementation in protecting biodiversity in TNGC and identifies obstacles in law enforcement. Using normative legal methods with a legislative and conceptual approach, this study analyzes the implementation of Law Number 5 of 1990 and Law Number 32 of 2009 in the context of TNGC protection. The results of the study indicate that despite a strong legal framework, biodiversity protection in TNGC still faces serious challenges. Around 42.54% of the total area has been degraded, indicating the complete ineffectiveness of existing regulations. The main obstacles include minimal human resources, low public awareness and participation, lack of infrastructure, conflicts of interest between the government and local communities, and complicated bureaucracy. This study concludes that an approach involving various stakeholders is needed to improve the effectiveness of biodiversity protection in TNGC. Recommendations include increasing the capacity of law enforcement, public education, improving infrastructure, conflict resolution, and bureaucratic reform. The implementation of this strategy is expected to strengthen conservation efforts and ensure the sustainability of the TNGC ecosystem for future generations.